Pertanggungjawaban Direksi BUMN dalam Perspektif Corporate Governance Atas Kerugian Keuangan Negara - Zukhruffiyah Rizqi Addinda; Dhifa Nadhira Syadzwina; Moza Fausta (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
The revision of the State-Owned Enterprises (SOE) Law fundamentally changes the concept of SOE losses by emphasizing that losses incurred in SOE operations constitute corporate losses, not state financial losses. This change has a direct impact on the construction of directors' accountability, which has often been associated with corruption when companies experience losses. This study aims to analyze the provisions of SOE directors' responsibilities based on Good Corporate Governance (GCG) principles within the new regulatory framework, as well as to examine the application of sanctions against directors who violate these principles and cause corporate losses. The study uses normative legal methods with statutory, conceptual, and case-based approaches. The analysis was conducted by examining the provisions of the Limited Liability Company Law, the revised SOE Law, related implementing regulations, and several important decisions, such as those concerning Jiwasraya, Asabri, Garuda Indonesia, and Pertamina-TPPI. The results show that the principles of GCG, fiduciary duty, and the Business Judgment Rule are the primary instruments in assessing directors' actions. Civil and administrative sanctions are the first line of defense for assessing directors' accountability, while criminal sanctions can only be imposed if there is an element of abuse of authority, conflict of interest, or other fraudulent acts. This research emphasizes the need for a clear distinction between business risks and unlawful acts to prevent directors from being criminalized for business decisions made in good faith and in accordance with good corporate governance principles. These findings are expected to serve as a reference in formulating state-owned enterprise policies and promoting more proportionate law enforcement against directors.